'Stateless' Rohingyas: persecution, displacement and complex community development. (2nd October 2020) - Jha, Manish K
Abstract: With complex sociopolitical contours around the idea of ethnicity, identity and citizenship, communities are experiencing unprecedented violence and vulnerabilities. The life and circumstances of one of such contentious community, Rohingya, is a telling example of an assault on their identity, culture, and history. The state sponsored violence and persecution had forced them to flee Myanmar. Denied recognition, as refugee or asylum seeker anywhere in the world, more than a million people from the community has become 'stateless' and living in a precarious condition in the camps in Bangladesh. This article explains the process whereby a community's identity and citizenship were undermined, forcing them to become a stateless community. The article explores: what role identity, ethnicity, and politics play vis-a-vis minority communities at the 'margin'? What complex challenges does it pose for community work and how community work attempts to take on that challenge? The article explains how sociocultural specificity poses a challenge for community workers to rely on their received wisdom. Therefore, approaches, strategies, and skills require substantive modification and alignment. Drawing upon personal interviews with key informants (coordinators of humanitarian response, community leaders, camp residents, and host community) and analysis of the documentary sources, the article brings forth the nature and character of community work undertaken by people coming from the varied disciplinary background.